Anomalous Chordae Tendineae Associated with Mitral Valve Dysplasia in a Cat - Guimarães, Laís Bitencourt; Serakides, Rogéria; Ribeiro, Lorena Gabriela Rocha; Ocarino, Natalia Melo (Brazilian Journal of Veterinary Pathology, 2013)
A rare case of anomalous chordae tendineae associated with mitral valve dysplasia was observed during necropsy in a 5- year-old male Persian cat with a history of sudden death. Grossly, there was thickening of the mitral valve, which was connected to numerous, short and thickened chordae tendineae that were ectopically inserted into the myocardium. In addition, marked left atrial dilation and pulmonary congestion and edema were present.